The Legal Effectiveness of Marriage Dispensation in the Religious Court of Batang, Central Java: A Case of Post-Law Number 16 of 2019 - Ali Trigiyatno; Makrum; Luthfi Hakim Arif Effendi (UIN K.H. Abdurrahman Wahid Pekalongan, 2023)
This research analyzes the factors contributing to the high number of marriage dispensation requests at the Religious Court of Batang Central Java following the enactment of Law Number 16 of 2019, which regulates the minimum age for marriage. A qualitative approach, employing deductive and inductive analyses, is utilized to comprehend the dynamics of this phenomenon. Positive transformation: Valuable data is collected through interviews, observations, and documentation, and skillfully transformed into insightful descriptive information. The research findings are anticipated to serve as a reference in the field of Islamic Family Law. The results indicate the ineffectiveness of legal provisions, evidenced by the substantial increase in marriage dispensation requests post the enactment of Law Number 16 of 2019. The judicial foundation for approving dispensation requests is rooted in the Quran, Hadith, Law Number 1 of 1974, Law Number 16 of 2019, Compilation of Islamic Law (HKI), and Supreme Court Regulation Number 5 of 2019. The practical implication underscores the need for a reevaluation of the marriage dispensation procedures to ensure better understanding among academics and the public. This research contributes innovatively by exploring the impact of Law Number 16 of 2019 on the phenomenon of marriage dispensation at the Religious Court of Batang, with a specific focus on legal effectiveness.